Characterization and Larvicidal Potency of Crude Urtica massaica Extracts Against Anopheles gambiae (Diptera: Culicidae) - Jared Yugi Owiti; Rose Khatoro Taabu; Rechab Odhiambo Sylvester; Nicholas Gitonga Mawira; Bethwell Owuor Onyango (علوم بهداشتی ایران)
Background and Purpose: Plants contain complex bioactive compounds with insecticide properties. The present study was designed to characterize and determine the larvicidal potency of crude methanol and hexane extracts of Urtica massaica against laboratory-cultured Anopheles gambiae larvae. Materials and Methods: This research was a laboratory-based experiment. Bioactive compounds were extracted using methanol and hexane, while larvae for bioassay were laboratory stock. The effectiveness of the extracts was evaluated using the World Health Organisation (WHO) >80% mortality threshold and methods, respectively. The extract dose was taken as the independent variable, while observed mortalities were the dependent variable. Dimethyl sulfoxide and distilled water were used as negative controls. Descriptive statistics and one-way analysis of variance were performed for statistical justifications of bioactive quantities and insecticidal properties of the extracts. Significant level was set at P<0.05. Results: Five groups of chemical compounds were extracted: Phenolic > amino acids and nitrogen derivatives>steroids and terpenoids > flavonoids, nitrogen derivatives, and others. Nineteen compounds were from roots, 17 from leaves, and 12 from stems. β-Sitosterol, 3,4-diferuloylquinic, and catechin were more while benzoic acid, L-leucine, N-(m-anisoyl)-, methyl ester, and myricetin were the least abundant in leaves, stem, and roots, respectively. Extracts from the stem killed more than 80% of exposed larvae for doses of 10 mL/100 cm3 (e/w) than those of the other parts (root and leaves). The observed mortalities, however, were not significantly different (P>0.05), irrespective of the dose or control used. Conclusion: U. massaica contains diverse bioactive compounds potent against A. gambiae larvae.